Exclusive Breastfeeding and Immunization as Determinants of Stunting Among Indonesian Children Under Five: Evidence from a Community-Based Case–Control Study - Nurhidayah, Ikeu; Khaedar, Mochamad; Herawati, Yanti; Koeryaman, Mira Trisyani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Stunting remains a major public health issue in Indonesia, reflecting chronic undernutrition and recurrent infections in early childhood. Exclusive breastfeeding and immunization are key interventions to promote healthy growth and child survival, aligning with SDG 2 (Zero Hunger) and SDG 3 (Good Health and Well-Being). However, evidence on their combined effects on stunting is inconsistent, especially in rural areas like Sumedang, where local data are limited. Objective: This study aimed to examine the association between exclusive breastfeeding, immunization status, and stunting among children aged 2–5 years in rural Indonesia. Methods: A community-based, case–control study involved 132 children (66 stunted and 66 non-stunted), aged 24–59 months. Data on stunting, breastfeeding, and immunization were collected via structured questionnaires and verified through child health records. Purposive sampling was used. Statistical analyses included descriptive statistics, Chi-square tests, and odds ratios (ORs) with 95% confidence intervals (CIs). Results: Children not exclusively breastfed had a significantly higher risk of stunting (p=0.001; OR=3.27, 95% CI: 1.48–7.22). Immunization completeness was not significantly associated with stunting (p=0.380; OR=1.36, 95% CI: 0.68–2.71). Conclusion: Exclusive breastfeeding offers strong protection against stunting and is vital for achieving SDG 2 and SDG 3. While immunization was not directly linked to stunting in this study, it remains essential for preventing infections that may indirectly impair growth. Strengthening breastfeeding promotion and community health programs are crucial for reducing stunting in rural Indonesia.